Biomedical Applications of Fermenticin HV6b Isolated from Lactobacillus fermentum HV6b MTCC10770. (29th July 2013) - Kaur, Baljinder; Balgir, Praveen P.; Mittu, Bharti; Kumar, Balvir; Garg, Neena
Abstract : Fermenticin HV6b is a class IIa antimicrobial peptide produced by Lactobacillus fermentum HV6b MTCC 10770 isolated from human vaginal ecosystem. It shows growth inhibition of a wide range of opportunistic pathogens of humans, for example, Bacteroides, Gardnerella vaginalis, Mobiluncus, Staphylococci, and Streptococci, associated with bacterial vaginosis in humans. It does possess an impressive sperm immobilization and spermicidal activity tested against human sperms which makes it an attractive proposition for formulating antibacterial vaginosis and contraceptive products. Apart from this, in vitro studies conducted against four different tissue models have indicated its potential to be used as a component of anticancerous drug therapy as it is reported to induce apoptosis in cancerous cells. This information could be integrated in future studies focusing on in vivo assessment of anticancerous activity of lactic acid bacterial toxins or bacteriocins.